Maternal and neonatel outcome among those with postdate pregnancy: Maternal and neonatel outcome among those with postdate pregnancy - Mohammed, Saba Abd Al Mahdi (Journal of the Faculty of Medicine Baghdad, 2019)
Background: Postdate pregnancy is that pregnancy, which goes beyond 40 weeks gestation being calculated from the first day of the last menstrual period and first trimester ultrasound. It occurs in approximately 10% of singleton pregnancies. Perinatal and maternal complications of such pregnancies have always been underestimated. Methods: A prospective case-control study of (600) pregnant women fulfilling the inclusion criteria( included: Gestational age range between (37 - 42 completed weeks), history of regular menstrual cycles and known date of the last menstrual period and/or with early pregnancy ultrasound and a singleton pregnancy with vertex presentation ), divided into (250) pregnant women as case group (beyond 40weeks of gestation) and (350) pregnant women as control group (between 37 completed weeks to 40 weeks of gestation).These mothers were admitted to the labor room at Basrah Maternity and Child Hospital from [1st of January to 1st November 2018]. Objectives: The aim of this study is to identify whether the prolongation of pregnancy beyond the expected date of delivery has negative effects on the health of both the mothers and the neonate. Results: The majority of both cases and controls were between 18 and 30 years of age (62.4% and 56.3 % respectively).and multiparous (1_4) deliveries; 55.6% and 58% respectively). Among the cases, postpartum haemorrhage was the most frequent maternal complication (16.4%), followed by prolonged labour(15.2%), perineal tear (5.2%), cervical tear and shoulder dystocia (1.6% for both) . The newborns of postdate pregnancies tend to be heavier at birth, where (19.2 %) were macrosomic (birth weight ≥ 4000 g) and (51.6%) weighed (3500-4000g). The majority (77.6%) had an Apgar score of (≥ 7). Meconium stained liquor, meconium aspiration syndrome, admission to the neonatal intensive care unit and birth asphyxia occurred in (23.2%, 12.4%, 18.8% and 1.2%) respectively. There were no birth injuries, intrauterine growth retardation or stillbirth in both cases and controls. Conclusion: In postdate pregnancies, there is a definitive risk on mother and baby.